Who seeks Internet-based interventions for depression in Brazil? - Lopes, Rodrigo Teixeira (2020)
Specific psychological treatments for depressive disorders delivered on the Internet have shown effectiveness and presented advantages over face-to-face treatments (potentially less expensive, flexible schedules, available in remote areas). This paper aims to describe the characteristics of those who sought help from an online self-guided intervention for depression and to explore hypotheses about predictors of enrollment to the program. Based on a sample of 282 of individuals who filled in screening questionnaires, we verified that the respondents were mainly female, were on average 34.36 years old, were primarily recruited through Facebook, had been previously diagnosed by mental health professionals, presented moderate self-efficacy perception, and had moderately severe symptoms of depression. Respondents who reported comorbid conditions were more likely to attend enrollment interviews, and being in treatment or not did not influence attendance. Such characterization may provide strategies to reach more people and to optimize the design of interventions targeting help-seeking depressed individuals in Brazil.